Handicrafts from Jalapao (TO), Brazil, and their relationship to plant anatomy - Eichemberg, Mayra Teruya [UNESP]; Scatena, Vera Lucia [UNESP] (Torrey Botanical Soc, 2011)
EICHEMBERG, M. T. and V. L. SCATENA (Universidade Estadual Paulista, Departamento de Botanica, Rio Claro, São Paulo, Brazil). J. Torrey Bot. Soc. 138:34-40. 2011.-Handicrafts from Jalapao (TO), Brazil, and their Relationship to Plant Anatomy. In the state of Tocantins, midwestern Brazil, communities from the region of Jalapao use scapes of "capim dourado" (golden grass - Syngonanthus nitens- Eriocaulaceae) and leaves of "buriti" (Mauritia flexuosa - Arecaceae) to make handicrafts (baskets and ornaments). The predominant biome of this area is cerrado (savanna), with a notable presence of buriti in the "veredas" (swampy forest-like vegetation), and of golden grass, which is one of the most common plants in humid grasslands. These traditional handicrafts represent a significant source of income for local communities. The whole scapes of Syngonanthus nitens are used due to their golden color, which is a reflection of such internal structures as thick walled cells and lignin in the epidermis and cortex. The strips called "seda" (silk) used to sew the scapes in the making of handicrafts come from young leaves of Mauritia,flexuosa. They are constituted by the adaxial epidermis and bundles of subepidermic fibers, both showing thick-walled cells. Since the cells of the bundles of sclerenchymatic fibers from the abaxial surface of buriti leaves present stegmata containing silica bodies, their mechanical properties are less adapted to the production of "silk", justifying the use of the leaf adaxial surface. Anatomical characteristics such as the thickening and composition of the cell walls of both species together with sociocultural factors, allow a better knowledge of the use of plant structures in the making of handicrafts.
Keywords: humid grassland; Mauritia flexuosa; savanna; Syngonanthus nitens